2021
DOI: 10.1101/2021.01.06.21249325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pregnancy and neonatal outcomes of COVID-19 – co-reporting of common outcomes from the PAN-COVID and AAP SONPM registry

Abstract: BackgroundFew large, cohort studies report data on individual’s maternal, fetal, perinatal, and neonatal outcomes associated with SARS-CoV-2 infection in pregnancy. We report outcomes from a collaboration formed early during the pandemic between the investigators of two registries, the UK and global Pregnancy and Neonatal outcomes in COVID-19 (PAN-COVID) study and the US American Academy of Pediatrics Section on Neonatal Perinatal Medicine (AAP SONPM) National Perinatal COVID-19 Registry.MethodsPAN-COVID (susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
136
2
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(153 citation statements)
references
References 20 publications
9
136
2
6
Order By: Relevance
“…Allotey J et al suggest that pregnant women with symptomatic SARS-CoV-2 infection are less likely to present with fever and myalgia, but are more likely to need intensive care, ventilation, and have a higher risk of pre-term delivery [19,20]; moreover, death occurs in a small number of cases that are COVID-related [21][22][23][24]. Among the 71 placentas we analyzed, there were no cases of the maternal-fetal transmission of SARS-CoV-2, and all the newborns were in good health at birth, with similar APGAR scores at 1 minute and 5 minutes to those of the controls (p = 0.83).…”
Section: Discussionmentioning
confidence: 99%
“…Allotey J et al suggest that pregnant women with symptomatic SARS-CoV-2 infection are less likely to present with fever and myalgia, but are more likely to need intensive care, ventilation, and have a higher risk of pre-term delivery [19,20]; moreover, death occurs in a small number of cases that are COVID-related [21][22][23][24]. Among the 71 placentas we analyzed, there were no cases of the maternal-fetal transmission of SARS-CoV-2, and all the newborns were in good health at birth, with similar APGAR scores at 1 minute and 5 minutes to those of the controls (p = 0.83).…”
Section: Discussionmentioning
confidence: 99%
“…Majority of COVID-19 infection in pregnancy will be asymptomatic. Preg COV-19 Living systematic review reporting on universal screening in pregnancy found 74% (95% CI 51-93) of women were asymptomatic [16]. While another study from the USA reported that 86% of women who were admitted in labor and who tested positive for SARS-CoV-2 were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Most symptomatic women experience only mild or moderate cold/flu-like symptoms. [18] The PregCOV-19 systematic review has so far included over 64 000 pregnant women worldwide with suspected or confirmed COVID-19 (reported prior to 29 November 2020) [16]. In this review, the most common symptoms of COVID-19 in pregnant women were cough (41%) and fever (40%).…”
Section: Discussionmentioning
confidence: 99%
“…Mütterliche Sterblichkeit war in beiden Registern selten: Sie trat bei 3 von 651 (0,46%) der Frauen mit bestätigter COVID-19 im PAN-COVID-Register und bei 5 von 2398 Frauen mit COVID-19 (0,21%) im AAP SONPM-Register auf. Diese Müttersterblichkeitsraten sind damit als höher einzuschätzen als die zuvor in diesen Bevölkerungsgruppen verzeichneten Müttersterblichkeitsraten (AAP SONPM-Register 167 pro 100 000) für Frauen, die zum Zeitpunkt der Geburt an COVID-19 erkrankt sind), verglichen mit einer Prä-COVID-Rate von 17,3 pro 100 000 in den USA) 169 . Das britische UKOSS-Register berichtet eine Müttersterblichkeitsrate von 2,2 pro 100 000 (95% KI 0,9–4,3) 42 122 .…”
Section: Hintergrundinformationen Zu Sars-cov-2 Und Covid-19 In Der S...unclassified